Training on the Use of Virtual Practicum Modules in Learning At SMP/Equivalent in Lhokseumawe City - Nuraini Fatmi; Iryana Muhammad; Sri setiawaty (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
This service is carried out at junior high/equivalent level schools in Lhokseumawe City. Based on the results of initial observations through interviews, it was found that virtual practicum activities are still rarely carried out in a number of schools in Lhokseumawe City. To provide a learning space outside the classroom, virtual practicum is a learning solution when students need knowledge outside of learning hours. This service is carried out in depth towards a situation or condition in a systematic way starting from making observations, collecting data, analyzing information and reporting results. The results of the dedication were obtained through a closed questionnaire which was used to find out things that support the implementation of virtual practicum. From the results of the questionnaire, it was found that the implementation of learning through virtual practicum books was very effective, this can be seen from the final practicum report, students obtained a score of 100%, which means students understand the use virtual books and able to make the final practicum report perfectly